(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
An integral part of the history of Uzbekistan, the attention to the study of the history of the Sughd confederation is increasing. After all, in the early Middle Ages, Sughd occupied an important place in the development of the Central and Far Eastern regions. This situation is closely related to Sughd’s favorable geographical location, active participation in international trade, economic relations, and high level of social life.